Co‐creating patient‐oriented discharge instructions with patients, caregivers, and healthcare providers. Issue 12 (25th September 2015) - Hahn‐Goldberg, Shoshana; Okrainec, Karen; Huynh, Tai; Zahr, Najla; Abrams, Howard
Abstract : For hospitalized patients, the transition from hospital to home is frequently accompanied by a significant amount of information to absorb. The objective of this work was to engage patients, caregivers, and healthcare providers in codeveloping patient‐oriented discharge instructions, (ie, a brief transition plan with information that patients want). Overseen by a multidisciplinary advisory team, a participatory action approach using mixed methods was employed. Although formal inclusion and exclusion criteria were not used, deliberate efforts were made to engage groups with language barriers and limited health literacy. Symbols were designed and validated with the patient groups to represent each section of information to make the form more understandable for these patients. A prototype was codesigned using an iterative process. The form has been adapted for use in multiple health settings and is currently undergoing a multisite pilot to evaluate its effect on patient and provider experience. Journal of Hospital Medicine 2015;10:804–807. © 2015 Society of Hospital Medicine